Cross-curricular skills testing in The Netherlands - Meijer, Joost (The Curriculum Journal, 2007)
This article gives a description of three analyses concerning the construct learning to learn and the assessment of cross-curricular skills. First, the correspondence between learning to learn and cross-curricular skills is examined by means of a theoretical content analysis. Second, the nature of cross-curricular skills is studied through a statistical analysis of the relation of these skills with intelligence, academic achievement and social-affective measures. Third, differences in the mastery of cross-curricular skills between two cohorts of students in Dutch secondary education were analysed statistically. The theoretical content analysis suggests that there are similarities between the learning to learn concept and cross-curricular skills, but the correspondence may be moderate. Cross-curricular skills appear to have more in common with academic achievement than with intelligence, suggesting that they are quite educable. Furthermore, they are moderately related to social-affective characteristics. It appears that a cohort of Grade 9 students who were tested for their cross-curricular skills in 1998 did considerably better compared to a cohort of Grade 9 students who were tested in 1996. There are some indications that this improvement may be related to the attention to these skills in schools.
Keywords: Pays-Bas; compétence; évaluation; évaluation des élèves